An aptamer‐based paper microfluidic device for the colorimetric determination of cocaine. Issue 3 (25th September 2017) - Wang, Ling; Musile, Giacomo; McCord, Bruce R.
Abstract: A method utilizing paper microfluidics coupled with gold nanoparticles and two anticocaine aptamers has been developed to detect seized cocaine samples. The ready‐to‐use format involves the use of a paper strip that produces a color change resulting from the salt‐induced aggregation of gold nanoparticles producing a visible color change indicating the presence of the drug. This format is specific for the detection of cocaine. The visual LOD for the method was 2.5 μg and the camera based LOD was 2.36 μg. The operation of the device is easy and rapid, and does not require extensive training or instrumentation. All of the materials utilized in the device are safe and environmental friendly. This device should prove a useful tool for the screening of forensic samples.